Effect of Galohgor Cookies Intake by Postpartum Mother on Newborn’s Growth - Ibnu Malkan Bakhrul Ilmi; Rimbawan Rimbawan; Katrin Roosita; Zakiudin Munasir (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: Malnutrition is one of serious public health problems that still need treatment priority. Besides the problem of over-nutrition continues to increase, the problem of under-nutrition has not been resolved properly. Utilization of local food such as galohgor can be an alternative to meet the nutritional needs. Objectives: The present study was aimed to analyze the effect of galohgor cookies intake by postpartum mothers on the newborn’s growth. Methods: The design was quasi-experimental design. There were two groups including the control group (CG) (n = 9) and the intervention group (GG) (n = 9). Postpartum mothers aged 20-35 years (parity between 2 and 5) with normal delivery and had no medical indication were involved in this study. A total of four pieces of cookie ( 4 g of galohgor powder) were consumed daily from the 1st day until the 40th day after delivery. Anthropometric data (height, body weight, and head circumference) were obtained on day 0, 14 and 40 after delivery. Meanwhile, human milk samples were taken on day 14 and 40 to analyze the levels of human milk insulin-like growth factor-I (IGF-I). Results: The newborns in the GG had significantly heavier weight and larger head circumference than CG on day 14 and 40 after delivery (p <0.05). IGF-I could be maintained by consuming galohgor during postpartum period. However, this study found no differences in body length of both control and intervention group (p> 0.05). Conclusions: Intake of galohgor cookies by postpartum mothers might support the newborn’s growth.